Unconditional positive self-regard, intrinsic aspirations and authenticity: pathways to psychological well-being - Murphy, David; Joseph, Stephen; Demetriou, Evangelia; Karimi Mofrad, Pegah (SAGE, 2017)
Unconditional positive self-regard (UPSR) is regarded by humanistic psychologists as an important determinant of well-being. However, until recently it has received little empirical attention. The current study aims to examine the association between unconditional positive self-regard and several key constructs consistent with the ideas of well-being within contemporary positive psychology. Study 1 is a confirmatory factor analysis of the UPSR scale. The statistically significant best fit for the data was a related two-factor model. Study 2 used the two-factors of the UPSR scale to explore the association with intrinsic aspirations. The study showed positive self-regard was statistically significantly positively correlated with the intrinsic aspirations total scale and with each of the separate scores for IA-importance and IA-chance. Unconditionality of regard was statistically significantly negatively correlated with IA-importance but was not statistically significantly correlated to either the IA-total or IA-chance scores. Study 3 considers the association between UPSR, intrinsic aspirations and authenticity. Unconditionality of regard was statistically significantly positively correlated with the authenticity scale score. Only IA-chance scores showed a statistically significant and positive correlation with authenticity. The remaining correlations between intrinsic aspirations and authenticity were not statistically significant. Results call for further empirical attention to UPSR within positive psychology research.